Cerebral microhemorrhage and iron deposition in mild cognitive impairment: susceptibility-weighted MR imaging assessment - Haller, Sven; Bartsch, Andreas J.; Nguyen, Duy; Rodriguez, Cristelle; Emch, Joan; Gold, Gabriel; Lovblad, Karl O.; Giannakopoulos, Panteleimon (Radiology, 2010)
Purpose - - To test whether susceptibility-weighted magnetic resonance imaging at baseline may help predict cognitive decline. - - Materials and Methods - - This prospective study was approved by the institutional review board, and written informed consent was obtained from all participants. Thirty-five healthy control subjects and 69 patients with mild cognitive impairment were included. Patients with mild cognitive impairment underwent neuropsychologic follow-up after 1 year (40 patients with stable mild cognitive impairment, 27 with progressive mild cognitive impairment, and two lost to follow-up). Cerebral microhemorrhages were visually analyzed by two experienced neuroradiologists in consensus. Iron deposition in deep gray matter was assessed with voxel-wise and region-of-interest analysis after nonlinear spatial registration. In addition, individual classification of mild cognitive impairment was analyzed by using a support vector machine (SVM). - - Results - - At baseline, the number of cerebral microhemorrhages was significantly higher in the mild cognitive impairment group than in the control group (P < .01) but did not differ between the patients with stable and those with progressive mild cognitive impairment. Compared with the control group, patients with mild cognitive impairment had increased iron concentration in the right pallidum (P < .01) and right substantia nigra (P < .01) but decreased concentration in the right red nucleus (P < .05). The classification based on the SVM successfully helped discriminate patients with mild cognitive impairment from the healthy control subjects (accuracy, 84%; sensitivity, 89%; specificity, 85%) and those with stable from those with progressive mild cognitive impairment (accuracy, 85%; sensitivity, 84%; specificity, 83%). - - Conclusion - - The findings reveal an accumulation of cerebral microhemorrhage in patients with mild cognitive impairment that is present at baseline, independent of subsequent cognitive decline, as well as an altered iron distribution in subcortical nuclei between the healthy control subjects and patients with mild cognitive impairment. Analysis of iron deposition at baseline performed with an SVM might help identify individual patients with mild cognitive impairment at risk for cognitive decline. - - © RSNA, 2010 - - Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10100612/-/DC1